Multilineage immune-mediated cytopenias in childhood: A report of five patients - (:unkn) unknown (My University, 2000)
This study was performed to determine whether there is any distinction to be made between single and multiple-lineage cytopenias particularly with regard to natural history and prognosis. From December 1989 to May 1994, five of 50 children (median age 7 years) with chronic immune cytopenias were diagnosed with multi-lineage immune-mediated cytopenias. Two patients presented with immune thrombocytopenia (ITP) and later developed autoimmune hemolytic anemia (AIHA); one had ITP and immune neutropenia who subsequently became Coombs' positive but never developed AIHA. One child presented with ITP and immune neutropenia and later developed AIHA. The fifth child presented simultaneously with thrombocytopenia and neutropenia with positive antineutrophil antibody but without antiplatelet antibody and Coombs' positivity. Four patients were given primary therapy with IVIG and one with prednisone. One patient responded to prednisone but relapsed subsequently. Further treatment with IVIG produced initial normalization of his counts with occasional fluctuation of the absolute neutrophil count. Two responded to IVIG and are in complete remission (CR). Of the two nonresponders to IVIG, one responded subsequently to prednisone and is in CR. The other one, after being refractory to multimodality treatment, was diagnosed with a lupus erythematosis variant and is currently on alternate day prednisone. Moderate thrombocytopenia and absolute neutropenia still persist. Multi-lineage immune-mediated cytopenias may represent a pathogenic phenomenon that is distinct from autoimmune single-lineage disease. Clinical response to treatment may correlate with these differences that may be genetic in origin. Clinical course and response to therapy are less predictable when autoimmune disease is present.
Keywords: Childhood; Evans syndrome; Multi-lineage autoimmune cytopenias